PENGARUH PENGGUNAAN VIDEO EDUKASI PENGELOLAAN DAN PENANGANAN SAMPAH TERHADAP SIKAP SISWA SEKOLAH DASAR DI KOTA MAKASSAR - Anis Kurniawan; Hamsu Abdul Gani; Erma S. Sahabuddin (Pascasarjana Universitas Negeri Makassar, 2021)
This study aims to determine the knowledge and attitudes of SD Negeri Borong Makassar students in managing and handling waste in the school environment. This research is a quantitative research with a correlational approach with one group pretest posttest design. The population in this study were all students of Class V and Class VI. The sample collection technique uses saturated sampling or the entire population is used as a sample. The data collection technique of this research is using tests, questionnaires and direct observation in the field. The data were then analyzed using descriptive statistics and T test with the help of SPSS 21.0. The results showed that the knowledge and attitudes of Class V and Class VI students before and after receiving environmental education video-based learning experienced a significant increase based on a descriptive analysis of the value of students' knowledge and attitudes after being given an educational video in the very high category regarding waste management and handling in the environment. school.